(untitled) (Homoeopathy for All, 2025)
The immune system is a complex network responsible for maintaining the body’s defence against pathogens and internal imbalances. Homeopathy, a system of medicine founded on the principle of "similia similibus curentur" (like cures like), offers a holistic approach to immune modulation. Rather than directly stimulating immune function, homeopathy aims to restore internal balance by addressing the individual’s physical, emotional, and energetic state. This article explores the conceptual basis of immune health in homeopathy, clinical applications in both acute and chronic conditions, and the current state of scientific evidence.